2003
DOI: 10.1074/jbc.m208075200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Phosphorylates Protein Kinase D Activation Loop Ser744 and Ser748 and Releases Autoinhibition by the Pleckstrin Homology Domain

Abstract: Persistent activation of protein kinase D (PKD) via protein kinase C (PKC)-mediated signal transduction is 744 and Ser 748 phosphorylation, concomitant with persistent 2-3-fold increases in PKD activity, measured using reimmunoprecipitated PKD to phosphorylate an exogenous peptide, syntide-2. We also further examined pleckstrin homology domainmediated PKD regulation to determine its relationship with activation loop phosphorylation. The high constitutive activity of the pleckstrin homology (PH) domain deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
193
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(204 citation statements)
references
References 64 publications
8
193
0
3
Order By: Relevance
“…GST or GST-c-jun fusion proteins (4 μg/time point) were phosphorylated by GST-PKD (90 ng/time point), in the presence of PS/PDB vesicles [7] and ATP (100 μM, with 2 μCi/time point [γ-32 P]ATP). SDS-PAGE gels were stained with Coomassie blue and dried, and c-jun fusion protein phosphorylation quantitated with a scintillation counter.…”
Section: Gst-c-jun Fusion Protein and C-jun Peptide Phosphorylation Rmentioning
confidence: 99%
See 1 more Smart Citation
“…GST or GST-c-jun fusion proteins (4 μg/time point) were phosphorylated by GST-PKD (90 ng/time point), in the presence of PS/PDB vesicles [7] and ATP (100 μM, with 2 μCi/time point [γ-32 P]ATP). SDS-PAGE gels were stained with Coomassie blue and dried, and c-jun fusion protein phosphorylation quantitated with a scintillation counter.…”
Section: Gst-c-jun Fusion Protein and C-jun Peptide Phosphorylation Rmentioning
confidence: 99%
“…PKDs, as well as several protein kinase C (PKC) isoforms, are directly stimulated by the second messenger diacylglycerol. Further, PKDs have emerged as effectors of novel PKC isoforms including PKCε and PKCη, which directly phosphorylate and activate PKDs in novel protein kinase cascades [6,7]. PKD, activated via PKC-mediated activation loop phosphorylation, exhibits dynamic spatiotemporal behavior including nucleocytoplasmic shuttling [6].…”
mentioning
confidence: 99%
“…For example, G-proteincoupled receptors or receptor tyrosine kinases that activate PLC and PKCε or PKCη cause the phosphorylation of PKD at Ser744 and Ser748 in the activation loop [16][17][18][19] . Second, Gβγ subunits directly activate PKD1 [20][21][22] .…”
Section: The Pkd Family Belongs To the Camk Groupmentioning
confidence: 99%
“…Unlike other PH domains that bind to lipids, the PH domain in PKD1 can bind to several proteins. Mutations in the PH domain can activate PKD1 [17,24,25] . Deletion of the two zinc-fi ngers also fully activates PKD1 [26,27] .…”
mentioning
confidence: 99%
“…The N‐terminal regulatory region encompasses an alanine/proline rich region (AP region), a tandem C1 domain binding diacylglycerol (DAG) and phorbol esters, an oligomerization domain, and a pleckstrin homology (PH) domain 24, 25, 26, 27, 28. Deletion mutagenesis approaches have indicated that the C1 and PH domains have an autoinhibitory effect on kinase activity, which is alleviated by activation loop Ser‐738/742 phosphorylation (hPKD1 numbering) 24, 25, 26. These phosphorylations are exerted by several PKCs, but PKDs can also autophosphorylate on Ser‐738 and Ser‐742 in vitro , and on Ser‐742 in cells 29, 30.…”
mentioning
confidence: 99%